Social group interactions in the fourth century BC Athens - Akgül, Tuğçe. (Thesis (M.A.) - Bogazici University. Institute for Graduate Studies in the Social Sciences, 2021., 2021)
The focus of this study is social group interactions in the context of Athenian society during the fourth-century BC. Rather than focusing on social order proposed by the laws, this thesis analyzes the relationships and links built by social groups and defines individuals’ position in Athenian society. This thesis argues that Athenian society had complex social relations than it was shown in the studies examining social groups and statues. To show intricate relationships and networks of the individuals, this study provides three case studies drawn from the fourth-century-BC Athenian court speeches: Pasion’s bank, Athenogenes’ perfume shop, and Neaira’s family. Each case points out different contexts where nonhierarchical relations and networking between social groups manifested themselves. The existence of such interactions brings a new dimension to the personal relationships in Athenian society. On the other hand, it questions our general assumptions and presents an alternative for Athenian social reality.
Keywords: Social groups -- Athens (Greece)